2015
DOI: 10.1542/peds.2014-3662
|View full text |Cite
|
Sign up to set email alerts
|

Estimated Number of Infants Detected and Missed by Critical Congenital Heart Defect Screening

Abstract: Background and objectives In 2011, the U.S. Secretary of Health and Human Services recommended universal screening of newborns for critical congenital heart defects (CCHD), yet few estimates of the number of infants with CCHD likely to be detected through universal screening exist. Our objective was to estimate the number of infants with nonsyndromic CCHD in the United States likely to be detected (true positives) and missed (false negatives) through newborn CCHD screening. Methods We developed a simulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
71
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(82 citation statements)
references
References 21 publications
1
71
0
6
Order By: Relevance
“…Despite screening, some infants may still go undetected. In 2015, Ailes et al [16], using a simulation study, estimated that of patients with nonsyndromic CCHD not diagnosed antenatally, as many as 50% will also not be detected by the present CCHD screening protocols. Large-scale population-based studies have demonstrated improved CCHD detection using pulse oximetry screening.…”
Section: Introductionmentioning
confidence: 99%
“…Despite screening, some infants may still go undetected. In 2015, Ailes et al [16], using a simulation study, estimated that of patients with nonsyndromic CCHD not diagnosed antenatally, as many as 50% will also not be detected by the present CCHD screening protocols. Large-scale population-based studies have demonstrated improved CCHD detection using pulse oximetry screening.…”
Section: Introductionmentioning
confidence: 99%
“…8 Modeling studies of the potential number of cases detected by screening for critical congenital heart disease in the United States suggest that screening could be cost-effective. 8,9 …”
mentioning
confidence: 99%
“…Даже в клиниках, где приме-няют аппарат ультразвуковой пренатальной диагно-стики экспертного класса и получают изображение сердца плода высокого качества, случаи недиагно-стированных критических пороков сердца достигают 10% [3]. В США в 2015 г. был представлен отчет в об-ласти педиатрии, в котором спрогнозирована позд-няя диагностика критических врожденных пороков сердца у 1755 новорожденных, половине из них по-мог бы скрининг пульсоксиметрии [4].…”
Section: перинатология и неонатологияunclassified